Investing in human capital for inclusive growth: Focus on higher education - Dante B. Canlas (Philippine Institute for Development Studies (PIDS), 2016)
What does the Philippines need to do to transform its economy into a high middle-income economy and ensure that the benefits from such a transformation are within reach of every Filipino? Investment in human capital, especially higher education, is one instrument that serves the twin goals of boosting economic growth with broad-based rewards, that is, inclusive growth. Currently, the Philippines is confronted by a low proportion of enrollees and graduates in higher and scientific education, and needs to raise its stock of labor with higher and scientific education amid rising demand for skilled workers and widening gaps in lifetime earnings between college and high school graduates. Several policies are indicated, but priority must be accorded to instituting loan programs for higher education, accelerating rationalization of the state university and college sector based on instituting regional university systems and centers of excellence, and devising grant programs for content standards for subjects and courses and formulating standardized tests for measuring and monitoring compliance with those standards applied to both public and private institutions of higher learning.
Keywords: 330